ANALISIS STRATEGI FRONTLINER DALAM MEMAKSIMALKAN LAYANAN NASABAH MENGGUNAKAN APLIKASI MUAMALAT DIGITAL ISLAMIC NETWORK (Studi Pada Bank Muamalat KC Payakumbuh) - Putra, Rehanzi; Kenedii, Jon (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The purpose of this study is to examine (1) How the strategies that have been carried out by frontliners in maximizing customer services using the Muamalat DIN (Digital Islamic Network) Application at Bank Muamalat KC Payakumbuh; (2) What are the obstacles and conveniences that customers feel when using the Muamalat DIN (Digital Islamic Network) application at Bank Muamalat KC Payakumbuh. This research is a field research using descriptive qualitative research methods. The subjects in this study are Bank Muamalat KC Payakumbuh, especially in the service department or frontliner of 3 people and several customers of Bank Muamalat KC Payakumbuh. The data collection technique in this study uses observation, interview and documentation techniques. The results of this study show that (1) In maximizing customer services using the Muamalat DIN Bank Muamalat KC Payakumbuh application. Bank Muamalat's frontliners implement customer service strategies and marketing mixes, by directly visiting customers, ATMs, SMS blasts, sales calls, and old mobile banking. (2) Based on the strategy that has been carried out by the bank frontliner, of course, there are obstacles and ease in carrying out their work. The obstacle faced was the problem of the network suddenly going down and when educating elderly customers to use Muamalat DIN. Meanwhile, the convenience felt is that it makes it easier to control account balances, saves in any aspect, and reduces transactions in the office